PERBEDAAN KEMAMPUAN KOMUNIKASI ANTARA PENGGUNAAN METODE PEMBELAJARAN CERAMAH DENGAN KOMBINASI CERAMAH DAN BERMAIN PERAN PADA MAHASISWA - Gunantari Ariani (Program Studi Sarjana Ilmu Keperawatan dan Profesi Ners, Fakultas Kedokteran, Universitas Udayana, 2014)
Implementation of nursing care, always keep the interactions between nurses and clients. The case based by understanding that, a good communication between nurses and clients takes an effect for the healthy of clients. The purpose of this research is to find the different effect of lecturer method with combination of lecturer and role playing method toward communication skill by regular students of PSIK FK UNUD. This type of this research use quasy experimental design. Those designs of this research use the approach of pre-test post-test with control group design. The sample of this research, divided by two groups that first group is intervening group that be given by lecturer and role playing method, and second group is control group that be given just lecturer method. Pre test and pos test are questionnaire and check list observation. The questionnaire has some questions about knowledge and attitude, and then the check list observant has some list of communication skill that the sample has to manage well. The results of the study, there were differences in communication skills both in the aspect of knowledge, attitudes and skills in the treatment group and the control group at pretest and posttest. There was no difference in enhancement of communication skill between intervening group and control group at aspect of knowledge (p value = 0,914) , attitude (p value = 0,58), but there was difference in communication skill at aspect of skill (p value = 0,01). There was no difference in communication skill between intervening group and control group at aspect of knowledge (p value = 0,271) , attitude (p value = 0,705), but there was difference in communication skill at aspect of skill (p value = 0,000).